2005
DOI: 10.1080/15419060500514168
|View full text |Cite
|
Sign up to set email alerts
|

Altered Tumor Biology and Tumorigenesis in Irradiated and Chemical Carcinogen-Treated Single and Combined Connexin32/p27Kip1-Deficient Mice

Abstract: Connexin32 knockout mice (Cx32-KO) exhibit increased chemical and radiation-induced liver and lung tumorigenesis. This increased tumor incidence is associated with altered tumor biology including enhanced tumor progression and an increased percent of MAPK-active tumors. Likewise, mice lacking the tumor suppressor/cell cycle regulator p27Kip1 exhibit increased tumorigenesis in a variety of tissues following chemical and radiation induction. Interestingly, in a double-deficient mouse model (DKO), additional loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
(90 reference statements)
1
4
0
Order By: Relevance
“…Furthermore, there are several documented cases where the exogenous expression of connexins in a transformed cell line can dramatically suppress its transformed properties and its ability to form tumors in nude mice [Cx43 in C6 glioma cells [ 11 ]; Cx43 in 10T1/2 embryonic mesenchymal cells [ 12 ]; Cx43 and Cx32 in LNCaP prostate cancer cells [ 13 ]; Cx26 in HeLa cervical cancer cells [ 14 ]; Cx26 and Cx43 in MDA-MB-231 breast cancer cells [ 15 , 16 ], and; Cx32 in SKHep1 hepatoma cells [ 17 ]. The latter is also consistent with an increase in hepatic tumorigenesis observed in Cx32-/- mice [ 8 , 18 ].…”
Section: Introductionsupporting
confidence: 84%
“…Furthermore, there are several documented cases where the exogenous expression of connexins in a transformed cell line can dramatically suppress its transformed properties and its ability to form tumors in nude mice [Cx43 in C6 glioma cells [ 11 ]; Cx43 in 10T1/2 embryonic mesenchymal cells [ 12 ]; Cx43 and Cx32 in LNCaP prostate cancer cells [ 13 ]; Cx26 in HeLa cervical cancer cells [ 14 ]; Cx26 and Cx43 in MDA-MB-231 breast cancer cells [ 15 , 16 ], and; Cx32 in SKHep1 hepatoma cells [ 17 ]. The latter is also consistent with an increase in hepatic tumorigenesis observed in Cx32-/- mice [ 8 , 18 ].…”
Section: Introductionsupporting
confidence: 84%
“…observed that effects on cell growth can occur independently of changes in channel activity, in casu GJIC [112,114,118,121,122,[142][143][144]148,156,160,[204][205][206][207][208][209][210][211][212][213][214][215]. In consistence with these observations is the fact that connexin proteins, as single entities, can affect the production and/or activity of cell growth regulators, including p27 Kip1 , cyclin A, cyclin D1, cyclin D2, cdk5, cdk6, ERK1/2, signal transducer and activator of transcription protein 3, Src, human EGF receptor 2, FGF1 and FGF receptor 3 which may [122,[142][143][144]152,155,169,[216][217][218][219][220][221] or may not [122,[142][143][144]148,156,160,209,212,222,…”
Section: Mechanisms Not Related To Connexin Channel Formation 4221 Modulation Of the Expression Of Cell Growth Regulators While Geneticalmentioning
confidence: 99%
“…For example, Cx32 is abundantly expressed in the hepatocytes, and knockout mice for this Cx exhibit a higher incidence of chemical-and radiation-induced liver tumors than their wild-type counterparts, respectively (Temme et al, 1997;Lampe, 2005a, 2005b). Also, Cx32 has been documented to act as a lung tumor suppressor, as assessed by higher bronchioloalveolar tumor incidence (King and Lampe, 2004;King et al, 2005aKing et al, , 2005b. Distinct dominant mutations in Cx26, a Cx abundantly expressed in the inner ear and skin, have been shown to cause not only hearing loss but also autosomal dominant disorders of epidermal keratinization and differentiation (Kelsell et al, 2001).…”
Section: Introductionmentioning
confidence: 99%